Teachers' knowledge and perception towards children with an autism spectrum disorder - G, Selvaganapathi; Thirupatharao V, Jinat Ahmed J, Mathialagan AG, Azra N, Kularaja k2, MHM Nazmul, KumaraswamyK,; M, Dinesh; T, Harikrishnan (Opción, 2019)
This study aims to assess teacher’s knowledge and perception towards children with autism spectrum disorder (ASD) in Malaysia. A cross-sectional study was done by using convenient sampling. Respondents that fulfill the inclusion & exclusion criteria were sent online validated questionnaire, data were analyzed using SPSS. As a result, only a few of the respondents have good knowledge of autism, however, more have a positive attitude towards autism. In conclusion, we found that teachers did, in fact, recognize their own lack of knowledge of ASD and this awareness co-existed with an interest in increasing their knowledge and skills in this area.